Autoantibodies in Pandemrix®-induced narcolepsy: Nine candidate autoantigens fail the conformational autoantibody test. (19th May 2019) - Wallenius, Madeleine; Lind, Alexander; Akel, Omar; Karlsson, Emma; Svensson, Markus; Arvidsson, Elin; Ramelius, Anita; Törn, Carina; Palm, Lars; Lernmark, Åke; Elding Larsson, Helena
Abstract: Study objectives: Narcolepsy type 1 (NT1) is a chronic sleep disorder characterized by loss of hypocretin-producing neurons. Increased NT1 incidence was observed in Sweden following mass-vaccination with Pandemrix ® . Genetic association to HLA DQB1*06:02 implies an autoimmune origin, but target autoantigen remains unknown. Candidate autoantigens for NT1 have previously been identified in solid-phase immunoassays, while autoantibodies against conformation-dependent epitopes are better detected in radiobinding assays. The aims are to determine autoantibody levels against nine candidate autoantigens representing (1) proteins of the hypocretin transmitter system; Preprohypocretin (ppHypocretin), Hypocretin peptides 1 and 2 (HCRT1 and HCRT2) and Hypocretin receptor 2 (HCRTR2); (2) proteins previously associated with NT1; Tribbles homologue 2 (TRIB2), Pro-opiomelanocortin/alpha-melanocyte-stimulating-hormone (POMC/α-MSH) and Prostaglandin D2 Receptor DP1 (DP1); (3) proteins suggested as autoantigens for multiple sclerosis (another HLA DQB1*06:02 -associated neurological disease); ATP-dependent Inwardly Rectifying Potassium Channel Kir4.1 (KIR4.1) and Calcium-activated chloride channel Anoctamin 2 (ANO2). Methods: Serum from post-Pandemrix ® NT1 patients ( n  = 31) and their healthy first-degree relatives ( n  = 66) were tested for autoantibody levels in radiobinding assays separating autoantibody bound from free labelled antigen with Protein A-Sepharose. 125 I-labelled HCRT1 and HCRT2 were commercially available while 35 S-methionine-labelled ppHypocretin, HCRTR2, TRIB2, α-MSH/POMC, DP1, KIR4.1 or ANO2 was prepared by in vitro transcription translation of respective cDNA. In-house standards were used to express data in arbitrary Units/ml (U/ml). Results: All radiolabelled autoantigens were detected in a concentration-dependent manner by respective standard sera. Levels of autoantibodies in the NT1 patients did not differ from healthy first-degree relatives in any of the nine candidate autoantigens. Conclusions: None of the nine labelled proteins proposed to be autoantigens were detected in the radiobinding assays for conformation-dependent autoantibodies. The results emphasise the need of further studies to identify autoantigen(s) and clarify the mechanisms in Pandemrix ® -induced NT1.